As the Turkish Journal of Anaesthesiology and Reanimation Leaves Its 50th Anniversary Behind - Hatice Türe; Özge Köner; Ezgi Aytaç; Aslı Dönmez; Mois Bahar (Turkish Journal of Anaesthesiology and Reanimation, 2024)

(untitled)
The Turkish Journal of Anaesthesiology and Reanimation, established in 1972, is 50 years old now. The number of citations of the journal and the interest of national and international researchers are high. This success has been achieved by the editorial boards who have contributed to the journal since its establishment and the writers who have contributed to its development, and this success will continue to increase.